A Novel Vaccine Delivery Model of the Apicomplexan Eimeria tenella Expressing Eimeria maxima Antigen Protects Chickens against Infection of the Two Parasites - Tang, Xinming; Liu, Xianyong; Yin, Guangwen; Suo, Jingxia; Tao, Geru; Zhang, Sixin; Suo, Xun (Frontiers in Immunology, 2018)
Vaccine delivery is critical in antigen discovery and vaccine efficacy and safety. The diversity of infectious diseases in humans and livestock has required the development of varied delivery vehicles to target different pathogens. In livestock animals, previous strategies for the development of coccidiosis vaccines have encountered several hurdles, limiting the development of multiple-species vaccine formulations. Here we describe a novel vaccine delivery system using transgenic Eimeria tenella expressing immunodominant antigens of E. maxima. In this delivery system, the immune mapped protein 1 of E. maxima (EmIMP1) was delivered by the closely related species of E. tenella to the host immune system during the whole endogenous life cycle. The overexpression of the exogenous antigen did not interfere with the reproduction and immunogenicity of transgenic Eimeria. After immunization with the transgenic parasite, we detected EmIMP1’s and E. maxima oocyst antigens’ specific humoral and cellular immune responses. In particular, we observed partial protection of chickens immunized with transgenic E. tenella against subsequent E. maxima infections. Our results demonstrate that the transgenic Eimeria parasite is an ideal coccidia antigen delivery vehicle and represents a new type of coccidiosis vaccines. In addition, this model could potentially be used in the development of malaria live sporozoite vaccines, in which antigens from different strains can be expressed in the vaccine strain.